APLIKASI TEKNOLOGI UNMANNED AERIAL VEHICLE (UAV) UNTUK MENGIDENTIFIKASI TUTUPAN HUTAN DAN LAHAN DI UNIVERSITAS LANCANG KUNING - Ikhwan, Muhammad; Tri Ratnaningsih, Ambar; Lestari, Ika; Ikhsani, Hanifah (Fakultas Kehutanan Universitas Lancang Kuning, 2021)
Lancang Kuning University Campus (UNILAK) is one of the campuses that has a fairly wide area and has enormous potential, especially related to the use of space whose potential has not been maximally utilized to support the Tridharma activities of higher education. The lack of land use is due to a more detailed inventory of land cover types that have not yet been carried out so that data and information related to existing land cover types are still very minimal. So it is necessary to identify the type of land cover and land cover characteristics at the Unilak Campus, to obtain information and data for further use. Land cover is the mention of biophysical appearance on the surface of the earth consisting of areas of vegetation, open land, built up land, water bodies and wetlands. One of the activities carried out for land cover data collection is land cover inventory activity using applications in the senses and GIS to collect data on land cover types in the study area coverage. Information on the types of land cover can be obtained from land cover data inventory activities through ground check activities or data collection on land cover conditions in the field.